Study to Assess Level of Preoperative Anxiety in Patients Scheduled for Surgery - Khanal, Resha; Banjade, Prakash; Bhandari, Bibek; Sharma, Subhash Chandra; Rijal, Rika (Journal of Nepal Health Research Council, 2022)
Background: Pre-operative anxiety is unpleasant state of tension or uneasiness that results from patient doubt and fear before an operation. This study aims at assessing level of state and trait anxiety and other associated factors among preoperative patient.Methods: A descriptive cross-sectional study was done among 195 patients above 18 years of age planned for elective surgery the following day in different departments in tertiary care center. State and Trait Anxiety Inventory and self-designed semi structured pro-forma was used to assess anxiety and patient particulars respectively.Results: There were 195 patients in study among which 93(47.7%) underwent major surgery and 102 (52.3%) underwent minor surgery. The mean State Anxiety Score was 45.89±12.502. The mean Trait Anxiety Score was 43.17±9.342. State and Trait anxiety differed significantly in male and female patients. Trait Anxiety was associated with education and marital status.Conclusions: There was no significant difference in anxiety level in patient undergoing major and minor surgery. Male and female patients differed significantly in both State and Trait Anxiety.Keywords: Preoperative anxiety; state anxiety; trait anxiety